ADAPTASI PEDAGANG KONVENSIONAL DI TENGAH PERKEMBANGAN E-DAGANG (E-COMMERCE) DI SUKARAMAI TRADE CENTER PEKANBARU - Enjel Damayanti M; Yusmar Yusuf (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The development of technology today is very influential on various aspects of life. One of them is that people's lifestyles are becoming more modern and practical. This change also affects the consumption actions of people who prefer to shop through e-commerce. For this reason, this study aims to find out what strategies conventional traders do in the midst of the increasing development of ecommerce at Sukaramai Trade Center Pekanbaru. This study uses a descriptive method with a qualitative approach. Data collection in this study used three techniques, namely observation, interview and documentation techniques. By using the theory of adaptation strategies. The subject of this research used purposive sampling technique. In this study, there were 6 sources from 805 traders on two floors of the Sukaramai trade center. With this research, it is found that conventional traders at Sukaramai Trade Center are able to adapt and have strategies in adapting to the development of e-commerce. Therefore, conventional traders can increase their income and survive so as not to be eroded by change, namely by running e-commerce while maintaining conventional stores. Keywords: Adaptation, Conventional Traders, E-Commerce.